"The Financial Is the Main Issue, It's Not Even the Child": Exploring the Role of Finances in Men's Concepts of Fatherhood and Fertility Intention. Issue 4 (July 2018) - Hamm, Megan; Miller, Elizabeth; Jackson Foster, Lovie; Browne, Mario; Borrero, Sonya
Despite demonstrable need, men's utilization of sexual and reproductive health services remains low. This low utilization may particularly affect low-income men, given the disproportionate prevalence of unintended pregnancy in low-income populations. Bolstering men's utilization of sexual and reproductive health services requires understanding the services that are most relevant to them. Semistructured interviews about fatherhood, fertility intention, and contraceptive use were conducted with 58 low-income Black and White men in Pittsburgh, Pennsylvania. The interviews were analyzed using content analysis to determine common themes that were most relevant to the men interviewed. The primacy of financial stability emerged as a dominant theme in men's perceptions of fatherhood readiness, successful fathering, and fertility intentions. However, men had children despite feeling financially unprepared, and their contraceptive use was not always congruent with their stated fertility intentions. Some men described financial services as a feature of family planning services that they would find useful. Because of the salience of financial stability in preparation for fatherhood, integrating financial counseling and job skills training into the context of sexual and reproductive health services could be a useful structural intervention to increase men's use of family planning services and to provide them with the support they say they need as fathers.